A SAÚDE DA PESSOA IDOSA NA ATENÇÃO BÁSICA: processos, limites e possibilidades no caso do município de Teresina-Piauí - Alencar, Maria do Socorro Silva (2011)
This thesis aims to understanding and analyzing the actions and primary care services developed by the Family Health Strategy with the elder in the city of Teresina, Piauí, and as this process these actions are being shaped in attitudes of protection active and healthy aging and social guarantees to the elderly population. Methodology: The issue is linked with the dimensions: health practices offered in the basic units (health promotion, prevention and health education, group activities), political-institutional organization of care, the process of multiprofessional teamwork and training of professionals to handle the demands of the elderly and aging. Authors of the field evaluation of social policies, public health and social gerontology anchored the discussion. The object of study is located in the subject area Social Policy and Policy Evaluation and Social Programs, with emphasis on evaluation procedures for the establishment and implementation of National Health Policy for the Elderly (PNSPI) and the actions of HIPERDIA. The context and the research subjects were the network of health-care services of the Municipal Health Service and the territorial structure of the Regional Health - CRS north-central and seventeen (17) professionals, of which fourteen (14) of ten (10) teams from the Basic Health Units, and technician manager of the Management of Primary Care and technician of CRS north central: doctors, nurses, dentists, nutritionists, public health expert, practical nurses and community health workers. Qualitative research using case study in having the procedure for field research: direct observation, quantitative survey of indicators to classify the elderly by age, chronic disease and bedridden, interviews, and document analysis. The description and interpretation of the themes by triangulation of information anchored in the content analysis technique. Results and Discussion: Based on the perceptions of social actors involved in the Family Health on the limits and possibilities for health care for the elderly found that the implementation process and implementation of actions arising from PNSPI was still planning for the fledgling promotion actions active aging, healthy and self-employed with health practices fragmented and discontinuous; regarding the actions of HIPERDIA although a more consistent strategy in the care of elderly, some obstacles mentioned by the subjects also demonstrated a fragile process and to the teamwork and lack of professional training in health and aging. The health care of the elderly follows the biomedical model of individual care based on medical and nursing, with its rules introjected by these professionals, as opposed to those who observe the social determinants of contexts in which they are generated. These elements in themselves demonstrate the complexity of health care for the elderly in family health, moreover if we consider that the skills required for this care are not yet part of the formation processes of different subjects that are now part of the teams. Conclusion: The "new" paradigm of health care for the elderly that seeks to evaluate them from multidimensional functional abilities has not is a strategy, in this city, which is capable of transforming the technical care model of primary healthcare in a wider and more complex model, which can interfere with their quality of life and reaffirm the commitment to individual care and public health. Therefore, if there was progress in the proposed universal access and comprehensiveness of health care on the basis of SUS by the legal and institutional bias, this same progress has not been accompanied by effective action in family health. For the deadlocks persist in this strategy, because there is the implementation of actions to promote and protect the health of the elderly and aging active, healthy and independent in the current situation of Brazilian society, marked by social inequities.